2020
DOI: 10.1101/2020.09.08.287672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic selection to optimize doubled haploid-based hybrid breeding in maize

Abstract: Crop improvement, as a long-term endeavor, requires continuous innovations in technique from multiple perspectives. Doubled haploid (DH) technology for pure inbred production, which shaves years off of the conventional selfing approach, has been widely used for breeding. However, the final success rate of in vivo maternal DH production is determined by four factors: haploids induction, haploids identification, chromosome doubling, and successful selfing of the fertile haploid plants to produce DH seeds. Traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Combining DHs and marker-assisted selection (MAS) has resulted in a significant advancement of the breeding systems in many major crops (Tuvesson et al, 2007). Genomic selection (GS), as a recently emerged technology to predict the performance of plants without phenotyping, has proven to be effective in plant breeding (Li et al, 2020;Krishnappa et al, 2021).…”
Section: Plant Breeding Applications: From Lab To Fieldmentioning
confidence: 99%
See 3 more Smart Citations
“…Combining DHs and marker-assisted selection (MAS) has resulted in a significant advancement of the breeding systems in many major crops (Tuvesson et al, 2007). Genomic selection (GS), as a recently emerged technology to predict the performance of plants without phenotyping, has proven to be effective in plant breeding (Li et al, 2020;Krishnappa et al, 2021).…”
Section: Plant Breeding Applications: From Lab To Fieldmentioning
confidence: 99%
“…DH methods have been, and are being, used to accelerate the breeding programs in a variety of crop plants, including maize (Zea mays), barley (Hordeum vulgare), Brassica sp., wheat (Triticum aestivum), and several vegetable crops (Ho and Jones, 1980;Ferrie and Möllers, 2011;Krishnappa et al, 2021). Maize is a crop where such an increase in improvement efficiency has resulted in a significant increase in genetic gain (Li et al, 2020). Geiger et al (2013) reported that genetic variances and per se performance were substantially increased in haploids and DH in maize.…”
Section: Plant Breeding Applications: From Lab To Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical studies for predicting field performances of DH lines using genomic prediction have been reported in maize [ 6 , 7 , 8 , 9 ]. These studies demonstrated the usefulness of genomic prediction for preselection of DH lines in the early stage of a breeding pipeline.…”
Section: Introductionmentioning
confidence: 99%